Substituted pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines - a promising class of lipoxygenase inhibitors - V. V. Stavytskyi; I. S. Nosulenko; O. O. Portna; V. M. Shvets; O. Yu. Voskoboynik; S. І. Kоvalenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
The modern strategy of potential biologically active molecules search (“drug-design”) is based on several innovation approaches. The method of high thrоughрut biological screening and method of molecular modeling deserves the most attention among such approaches. Lipoxygenase (LOX) is one owf the most perspective biological target for the substituted pyrrolo[1,2-a][1,2,4]triazolo-(triazino-)[c]quinazolines. So, molecular docking towards LOX and enzyme activating activity was investigated.